The Quality of Spa Services in Unique Hotels Under The Crisis Conditions of a Pandemic Covid-19 And War in Ukraine - Wojciech SADKOWSKI; Krzysztof SALA (Communications of International Proceedings, 2024)
The motivation to undertake research was the willingness to diagnose the current situation of providing spa services in historic and boutique hotels during the difficult period of the global Covid-19 pandemic and the armed conflict in Ukraine. On the basis of a literature review based on scientific databases, an existing cognitive gap in the field of the latest research results was revealed, the subject of which would be a representative group of hotels from all over Poland, a concerning the impact of Covid-19 and the war in Ukraine on the quality of spa services. In order to fulfil the purpose of the publication, the questionnaire survey method was used. The research sample was a representative group of unique hotels providing spa services across Poland (104 hotels). They represented approximately 87% of all unique hotels in Poland. The results of the study indicate that neither the Covid-19 pandemic nor the war in Ukraine has had any meaningful impact on the quality of spa services provided in Poland’s unique hotels. Nevertheless, the consequences of the armed conflict in Ukraine are borne by Polish hotels in the form of additional costs incurred by these facilities.
Keywords: Covid-19 pandemic; quality management; service quality; unique hotels; war in Ukraine